2009
DOI: 10.1016/j.jcin.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Drug-Eluting Versus Bare-Metal Stents in Saphenous Vein Graft Intervention

Abstract: Treatment of SVG lesions with DES vs. BMS is effective in reducing TVR at 9 months, although most of this advantage is lost at 2 years. The DES seem safe with less death or myocardial infarction, although selection bias might have affected these results. Our data suggest that DES might have short-term advantages over BMS in SVG lesions with diameter <3.5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…[19] There seems to be a more pronounced early benefit while longer-term benefits seem less pronounced as described above. Recent observational data also suggested a late “catch-up” phenomenon regarding TVR with a clear benefit for DES in the first year but similar longer term results [49]. It seems plausible that, after the coating drug has completely eluted, the beneficial effect of DES compared to BMS decreases.…”
Section: Discussionmentioning
confidence: 88%
“…[19] There seems to be a more pronounced early benefit while longer-term benefits seem less pronounced as described above. Recent observational data also suggested a late “catch-up” phenomenon regarding TVR with a clear benefit for DES in the first year but similar longer term results [49]. It seems plausible that, after the coating drug has completely eluted, the beneficial effect of DES compared to BMS decreases.…”
Section: Discussionmentioning
confidence: 88%
“…A recent meta-analysis suggested that DES is associated with a lower need for reintervention and a lower mortality rate compared with BMS in patients who undergo PCI for vein bypass grafts 27 . However, DES does not show long-term advantages in these patients 28 . The sample of patients who received FMJ in vein grafts in our study was too small, thus limiting our ability to draw definite conclusions in this regard.…”
Section: Discussionmentioning
confidence: 80%
“…Multiple investigators have suggested a survival benefit of DES using conventional methods, such as propensity scores. 7, 9, 29, 30 In contrast, others using IV and related methods have generally shown no difference in mortality and stronger impacts on repeated revascularization than is observed with propensity scores. 3135 A natural question that emerges from these disparate lines of evidence is, “which one should be believed?” While the extensive trial data available for the DES versus BMS comparison are consistent with the IV results in this analysis, reliance on clinical trial results to validate any particular methodology (IV or PS in this case) is not necessarily appropriate in most applications.…”
Section: Discussionmentioning
confidence: 96%